Microinstabilities in hydrogen- and helium-dominated multi-ion-species plasmas in LHD. (9th March 2017) - Nunami, Masanori; Nakata, Motoki; Sugama, Hideo; Tanaka, Kenji; Toda, Shinichiro
Abstract: The ion scale microinstabilities in the large helical device (LHD) are investigated by the gyrokinetic simulations for the multi-ion-species plasmas including hydrogen, helium, and impurity ions. The observations in the LHD experiments show that the ion temperature increases with the decreases of the ratio of hydrogen density to helium density. It is found from the linear gyrokinetic simulations with the multi-ion-species and real-mass kinetic electrons in the LHD discharges that the growth rates of the ion scale microinstabilities are reduced for the helium-dominated multi-species plasma compared with the hydrogen-dominated one. In addition to the differences of the conditions including the temperature, the density profiles, and the temperature ratio between both plasmas, due to the dependence on the mass number and the electric charge of the mixed ion species, the mixing length estimates obtained from the linear simulations predicts smaller ion thermal diffusivity for the helium-dominated plasma than the hydrogen-dominated one in the hydrogen gyro-Bohm unit, which is consistent with the experimental results.